The Effect of Trade Secrets Law on Stock Price Synchronicity: Evidence from the Inevitable Disclosure Doctrine - Kim, Yongtae; Su, Lixin (Nancy); Wang, Zheng; Wu, Haibin (The Accounting Review, 2021)
ABSTRACT We exploit the staggered recognition of the Inevitable Disclosure Doctrine (IDD) by U.S. state courts to examine the effect of trade secret protection on the amount of firm-specific information incorporated in stock prices, as reflected in stock price synchronicity. We find that after certain state courts recognize the IDD, firms headquartered in those states exhibit a significant increase in stock price synchronicity relative to firms in other states. We also find a significant decrease in the disclosure of proprietary information in the firms' 10-K reports. These results suggest that IDD recognition increases the proprietary cost of disclosure and, in response, corporate managers withhold more information. In addition, we find that the increase in stock price synchronicity and the decrease in the disclosure of proprietary information lead to increases in the firm's market share, cost of equity, and market-to-book ratio, suggesting that managers sacrifice capital market benefits for product market gains. Data Availability: Data used in this study are available from public sources identified in the study.